2014
DOI: 10.1111/gbb.12157
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide search for quantitative trait loci affecting the cortical surface area and thickness of Heschl's gyrus

Abstract: Heschl's gyrus (HG) is a core region of the auditory cortex whose morphology is highly variable across individuals. This variability has been linked to sound perception ability in both speech and music domains. Previous studies show that variations in morphological features of HG, such as cortical surface area and thickness, are heritable. To identify genetic variants that affect HG morphology, we conducted a genome-wide association scan (GWAS) meta-analysis in 3054 healthy individuals using HG surface area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…This question may be approached using gene-set enrichment analysis and polygenic risk scores, in brain imaging genetics datasets produced for genome-wide association scanning (Cai et al, 2014;Guadalupe et al, 2015;Hibar et al, 2015;Thompson et al, 2014). Genetic association studies of individual candidate genes, that were not so far motivated by data on lateralized gene expression, have indicated that measures of languagerelated functional lateralization may associate with common genetic variants (Ocklenburg et al, 2013;Pinel et al, 2012).…”
Section: Figurementioning
confidence: 99%
“…This question may be approached using gene-set enrichment analysis and polygenic risk scores, in brain imaging genetics datasets produced for genome-wide association scanning (Cai et al, 2014;Guadalupe et al, 2015;Hibar et al, 2015;Thompson et al, 2014). Genetic association studies of individual candidate genes, that were not so far motivated by data on lateralized gene expression, have indicated that measures of languagerelated functional lateralization may associate with common genetic variants (Ocklenburg et al, 2013;Pinel et al, 2012).…”
Section: Figurementioning
confidence: 99%
“…Variation within DSE has been associated with several cancers (Gouignard et al, 2016a; Thelin et al, 2013, 2012), Heschl’s Gyrus thickness (Cai et al, 2014), and is also a notable risk factor for Ehlers-Danlos syndrome, with a subtype specifically linked to dysfunction of DSE (Müller et al, 2013). Recent work by Gouignard et al (Gouignard et al, 2016b) demonstrates a functional role for dse (the protein encoded by DSE ) in cranial neural crest cell migration and in cell adhesion providing a potential biological mechanism linking DSE dysfunction to Ehlers-Danlos syndrome and other neural crest related disorders (i.e., neurocristopathies); the knockdown of dse impaired the correct activation of transcription factors involved in the epithelial-mesenchymal transition and reduced the extent of neural crest cell migration, subsequently leading to a decrease in neural crest-derived craniofacial skeleton, melanocytes and dorsal fin structures.…”
Section: Discussionmentioning
confidence: 99%
“…This array only contains SNPs related to cardiovascular diseases and thus, the assumption of independence may not hold. We used instead an a priori defined threshold to define association in the discovery study, an approach used by other investigators analyzing quantitative traits [52]. Of importance, we were able to replicate our association in two independent populations where serum levels of IL8 were available.…”
Section: Discussionmentioning
confidence: 99%